Neuroinflammation in Low-Level PM2.5-Exposed Rats Illustrated by PET via an Improved Automated Produced [18F]FEPPA: A Feasibility Study - Cheng, Mei-Fang; Cheng, Tsun-Jen; Guo, Yue Leon; Chiu, Ching-Hung; Wu, Hung-Ming; Yen, Ruoh-Fang; Huang, Ya-Yao; Huang, Wen-Sheng; Shiue, Chyng-Yann (Molecular imaging, 2022)
Background. [18F]FEPPA is a potent TSPO imaging agent that has been found to be a potential tracer for imaging neuroinflammation. In order to fulfill the demand of this tracer for preclinical and clinical studies, we have developed a one-pot automated synthesis with simplified HPLC purification of this tracer, which was then used for PET imaging of neuroinflammation in fine particulate matter- (PM2.5-) exposed rats. Results. Using this automated synthesis method, the RCY of the [18F]FEPPA was 38±4% (n=17, EOB) in a synthesis time of 83±8 min from EOB. The radiochemical purity and molar activities were greater than 99% and 209±138 GBq/μmol (EOS, n=15), respectively. The quality of the [18F]FEPPA synthesized by this method met the U.S. Pharmacopoeia (USP) criteria. The stability test showed that the [18F]FEPPA was stable at 21±2°C for up to 4 hr after the end of synthesis (EOS). Moreover, microPET imaging showed that increased tracer activity of [18F]FEPPA in the brain of PM2.5-exposed rats (n=6) were higher than that of normal controls (n=6) and regional-specific. Conclusions. Using the improved semipreparative HPLC purification, [18F]FEPPA has been produced in high quantity, high quality, and high reproducibility and, for the first time, used for PET imaging the effects of PM2.5 in the rat brain. It is ready to be used for imaging inflammation in various clinical or preclinical studies, especially for nearby PET centers without cyclotrons.